The impact of drought coping strategies on food security in Zimbabwe: the case of Tsholotsho district. - Mugwagwa, Daisy (Midlands State University, 2017)
Zimbabwe is currently characterized by droughts caused by El Nino. The droughts have become a common feature for agriculture in Zimbabwe, a country whose majority of the population (70%) depends on agricultural based activities as their livelihoods resource. The research is carried out in Tsholotsho district ward 13 which is characterized by erratic and inadequate rainfall. Drought frequency is very high occurring at a rate of four in every five years. The main purpose of this research was to establish the drought coping strategies that are in place and to establish the impact of these drought coping strategies on food security in Zimbabwe. The researcher used questionnaires to collect data from participants in the research. Drought coping strategies which were discussed in the study included responses to production, consumption, food storage, income generating assets and livestock management, external assistance from the Government, NGOs and migration complimented these strategies. The research findings reviewed that the people in Tsholotsho district used external assistance from the government, NGOs and social networks like friends and relatives, migration, growing of drought resistant crops and sale of assets such as livestock. The results of the research established that government departments and NGOs were the actors involved in drought mitigation in the district. However it was also seen that these actors face challenges such as political interference, shortage of staff and inadequate resources such as transport and fuel. The research reviewed that there is need for the people in the community to add consumption response and food preservation to the existing drought coping strategies in place. The government is recommended to make sure that robust committees such as the DDR are created right up to the village level where the effects of drought are mostly seen. Whilst the NGOs are recommended to understand the local coping strategies and to work hand in hand with the community. Research findings led to a conclusion that most of the coping strategies employed by the people in the district contribute to food security in Zimbabwe.